Lossless compression scheme for efficient GNSS data transmission on IoT devices - Perez, R.; Correia, S.; Valderi Leithardt (International Conference on Electrical, Computer, and Energy Technologies, ICECET 2021, 2021)
Wireless data transmission is one of the most energy-consuming tasks performed on embedded devices, being a crucial feature of battery-powered Internet of Things (IoT) applications. The present work proposes a new methodology to reduce the energy footprint of GNSS-based sensors by decreasing the amount of transmitted data applying a lossless compression strategy. Online trajectory data is structured through a pre-processing stage without information loss and posteriorly com-pressed through standard lossless algorithms. Simulations are performed considering different trajectory shapes, comparing the proposed schema with traditional compression methods without the proposed pre-processing stage. The results show that the proposed scheme can reach lower compression rates, reducing embedded IoT devices' energy footprint.